2020
DOI: 10.1111/vec.13014
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between bispectral index value and modified Glasgow Coma Scale score in dogs with altered level of consciousness

Abstract: Objective This study aims to identify the correlation between bispectral index (BIS) value and modified Glasgow Coma Scale (MGCS) score in dogs with altered level of consciousness (ALOC). Design This prospective, observational, clinical study was conducted from February 2016 to March 2017, and follow‐up was conducted until the death of dogs or their discharge from the hospital. Setting This study was performed at the Small Animal Teaching Hospital. Animals A total of 31 client‐owned dogs (males, 20; females, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Compared with our study, some limitations were observed, the main one being the absence of a control group to link and verify the benefit of BIS associated with the TCI technique in this specific case with STCI. Another correlation between BIS values in dogs using the modified Glasgow Coma Scale score with altered levels of consciousness showed the efficiency of BIS in monitoring consciousness in patients with altered levels of consciousness [12]. However, studies directed to the applicability of BIS in dogs are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with our study, some limitations were observed, the main one being the absence of a control group to link and verify the benefit of BIS associated with the TCI technique in this specific case with STCI. Another correlation between BIS values in dogs using the modified Glasgow Coma Scale score with altered levels of consciousness showed the efficiency of BIS in monitoring consciousness in patients with altered levels of consciousness [12]. However, studies directed to the applicability of BIS in dogs are scarce.…”
Section: Discussionmentioning
confidence: 99%